Digital History Class of 2016 - Payne, Sarah, photographer (Colorado State University. Libraries, 2016)
Digital History Class of 2016 in front of Johnson Hall.
Top Row L-R: Mark Boxell, Nathan Varnold, Will Wright, Maggie Moss-Jones.
Center Row L-R: Sam Iven, Dane Vanhoozer, Emily Ann, Beth Hodgell, Jedediah Jackman, Katrina Cotter.
Bottom Row L-R: Poppie Gullett, Colin Behnke, Katrina Swolley, Andrew Viloudaki, Jessica Campbell, Shannon Kelly, Sean Fallon.
This work is provided by students of HIST 580A: Digital History for use on the StoryMap project: Colorado State University's Sense of Place.